2000
DOI: 10.1017/s0376892900000163
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and socio-economic impacts of Mediterranean marine protected areas

Abstract: SummaryMarine protected areas (MPAs) may be important for protecting the marine environment, but they may also have substantial socio-cultural impacts about which very little is currently known, or acknowledged. In the Mediterranean, few data are available on the socioeconomic consequences of MPAs. The present study reviews the existing data on MPAs in Spain, France, Italy and Greece. A general increase in tourist activities in Mediterranean MPAs is evident, as are increases in the abundances of larger fish sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
1
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(104 citation statements)
references
References 39 publications
0
96
1
7
Order By: Relevance
“…This higher density of fishing gear remains could be related to artisanal fishing activities occurring in these coastal marine protected areas, e.g. gillnets or long-lines (fishing gears that are deployed over the seabed, frequently rocky bottoms, and that can easily get entangled in the bottom and therefore abandoned there) (Gómez et al 2006, Badalamenti et al 2000, Sarda et al 2012.…”
Section: Spatial Distribution and Density Of Debrismentioning
confidence: 99%
“…This higher density of fishing gear remains could be related to artisanal fishing activities occurring in these coastal marine protected areas, e.g. gillnets or long-lines (fishing gears that are deployed over the seabed, frequently rocky bottoms, and that can easily get entangled in the bottom and therefore abandoned there) (Gómez et al 2006, Badalamenti et al 2000, Sarda et al 2012.…”
Section: Spatial Distribution and Density Of Debrismentioning
confidence: 99%
“…However, a nearly inevitable consequence of prohibiting fishing will be some cost or loss of utility to excluded user groups including recreational and commercial fishers (Badalamenti et al 2000, Sladek Nowlis & Friedlander 2005. Over time, spillover of adult fishes or enhanced export of larvae from no-take reserves may lead to net benefits to fishers in connected areas (McClanahan & Mangi 2000, Roberts et al 2001, 2004, Sladek Nowlis & Friedlander 2005; however, uncertainty as to the likely scale of such benefits in any given situation, together with the fact that protection needs to be effective for an extended period for a reserve to work as a fishery management tool (Russ & Alcala 1999), means that no-take reserves are not an unproblematic solution to balancing conservation with extractive use.…”
Section: Introductionmentioning
confidence: 99%
“…Tourism has significant potential as an MPA financing mechanism [15,[64][65][66] and may lead to economic benefits at a broader scale; however, the level of local community benefit from and involvement in tourism can be minimal. Some MPAs, such as the Great Barrier Reef MPA in Australia [67], Mendes Island MPA in the Mediterranean [68], and Tsitskamma National Park in South Africa [69], have resulted in significant increases in tourism visitation and revenue [51,70]. A global study of 78 coral reef MPAs found that 75% of tourism jobs were retained locally [71].…”
Section: Livelihood and Community Outcomesmentioning
confidence: 99%